Indonesia's Diplomacy Strategy in Maintaining Policy Stability amid the Global Situation - Ronika, Yulia Febi Zita; Sutanto, Rudy; Timur, Fauzia Gustarina Cempaka (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research explores Indonesia's diplomatic strategy in maintaining policy stability amidst the dynamics of the global situation, focusing on the RussiaUkraine conflict and its impact on the national economy. In the context of the free and active principle, Indonesia plays a crucial role as a mediator and stability maintainer, reflecting its commitment to neutrality and prudent foreign policy. The diplomatic challenges faced by Indonesia, especially pressure from Western countries, are explained as complex dynamics that require a careful approach. This research uses a qualitative method with a literature documentation study, covering theories of diplomacy, policy stability, international relations, development, and the global economy. The conclusion states that Indonesian diplomacy has a strategic role in maintaining policy stability and contributes directly to the achievement of the Golden Indonesia 2045 vision.